Data on survival of recent births as a source of child mortality estimates in the developing world: An assessment of census data. (1st September 2016) - Merdad, Leena; Hill, Kenneth; Levin, Michael
Abstract : In many less developed countries, household surveys collect full and summary birth histories to provide estimates of child mortality. However, full birth histories are expensive to collect and cannot provide precise estimates for small areas, and summary birth histories only provide past child mortality trends. A simple method that provides estimates for the most recent past uses questions about the survival of recent births in censuses or large household surveys. This study examines such data collected by 45 censuses and shows that on average they tend to underestimate under-5 mortality in comparison with alternative estimates, albeit with wide variations. In addition, the high non-sampling uncertainty in this approach precludes its use in providing robust estimates of child mortality at the country level. Given these findings, we suggest that questions about the survival of recent births to collect data on child mortality not be included in census questionnaires.